Perencanaan Ruang Gersang menjadi Taman Edukasi Dekarbonisasi dan Ruang Perokok Ramah Lingkungan di Universitas Annuqayah - Aditya Dandy Firatama; Raihan Firdaus; Efendi Pratama Putra (Universitas Muhammadiyah Surabaya, 2026)
This study analyzed the determinants of ecological participation of the academic community and formulated the design of smart smoking area integrated decarbonization education Park as a carbon footprint mitigation strategy at Annuqayah University using an explanatory sequential mixed methods approach through a survey of 60 respondents and interviews with 10 informants. Pls-SEM analysis shows that all constructs are valid and reliable (AVE 0.579-0.655; CR > 0.70), with structural results indicating that the perception of carbon footprint has the most dominant effect on ecological participation (③=0.234; p < 0.000), followed by decarbonization awareness (③=0.173; p = 0.003), environmental comfort (③=0.121; p = 0.012), and visual perception of space (③=0.069; p < 0.000). Qualitative findings reveal three main issues, namely limited open space comfort, weak implementation of decarbonization, and ecological participation that is still potential, which confirms the dominance of cognitive factors compared to physical in encouraging ecological behavior. Based on these findings, educational parks based on carbon-absorbing vegetation and smart smoking areas were designed that process cigarette butts into natural pesticides as an ecological-educational intervention to improve thermal comfort, environmental literacy, and participation activation towards a contextual and replicative low carbon campus model.